Characteristics and Outcomes of SARS-Cov-2 Positive Pregnant Women Admitted to a Dedicated COVID ICU in RMCH, Bangladesh: An Observational Study - Khatun, Wahida; Rahman, Md Akkasur; Kamal, Abu Hena Mostafa (TAJ: Journal of Teachers Association, 2023)
Background: The global pandemic caused by the SARS-CoV-2 virus has resulted in millions of infections worldwide, affecting individuals of all ages and genders. Pregnant women with comorbidities face an increased risk of severe COVID-19 infections, posing significant challenges to their clinical management in dedicated COVID-19 Intensive Care Units (ICUs). This single-centre observational study aimed to examine the characteristics and outcomes of COVID-19-positive pregnant women admitted to a dedicated COVID-19 Intensive Care Unit (ICU) at Rajshahi Medical College Hospital (RMCH) in Bangladesh. Methods: A observational study, analyzing data from pregnant women admitted to hospitals and adult COVID-19 ICUs between March 1, 2020, and December 31, 2021. A total of 21 patients were included in the analysis. Patient demographics, medical histories, gestational age, symptoms, laboratory findings, and clinical outcomes were recorded and analyzed. The primary outcomes assessed were maternal mortality at 30 and 60 days, while the secondary outcomes included the length of ICU and hospital stay, fetal mortality, and preterm delivery. Results: Among the 21 pregnant patients admitted to the COVID-19 ICU, 10 were COVID-positive, and 11 were suspected COVID cases. A total of 11 patients experienced adverse outcomes, resulting in a 52.4% mortality rate. None of the patients had received vaccination against COVID-19. Conclusion: This single-centre observational study provides valuable insights into the characteristics and outcomes of COVID-19-positive pregnant women admitted to a dedicated COVID-19 ICU at RMCH, Bangladesh. Pregnant women with underlying comorbidities may be at a higher risk of severe COVID-19 illness, warranting close monitoring and timely interventions. The study underscores the importance of tailored clinical management strategies for pregnant women infected with SARS-CoV-2 to improve maternal and fetal outcomes. Further, multi-centre studies are warranted to validate and expand upon these findings, contributing to the global understanding of COVID-19 in pregnancy. TAJ 2023; 36: No-2: 25-33